An Innovative Extension Model for Integrated Rural Development: A Case of Samaj Shilpi Dampati Scheme - Manjunatha, B. L.; Rao, D. U. M.; Singh, Rashmi (Indian Journal of Extension Education, 2016)
The research study conducted in Chitrakoot district of Uttar Pradesh state in India was aimed to study the philosophy,  origin, process and functioning of the Samaj Shilpi Dampatis (SSD) scheme along with its socio-economic impact on  livelihood of the villagers. SSDs live in a village and work for a cluster of five villages. This cluster of five villages is  called a SSD unit. One village was selected randomly from each SSD unit. Twenty farmer households were selected  randomly from each village. Totally, 100 farm households were interviewed for primary data collection. Five SSDs (10  functionaries) and twenty officials working in various organizations of DRI were also selected for primary data collection.  The study found that SSDs, the grassroots level functionaries, possessed a very high level of achievement motivation,  organizational commitment, dedication, faith in people, empowerment, and development orientation. The scheme had a  great impact on beneficiaries in their raise in income, savings, and increase in employment days. Majority of the  respondents, especially marginal and small farmers, adopted either 1.5 or 2.5 acre model that helped ensure food security  for their families throughout the year. Adoption of kitchen gardens in their homesteads helped secure nutritional security  for the family. The village sanitation, health and hygiene of respondent households had improved a lot. More than 85 per  cent of the families shifted from below poverty line category to above poverty line category. The SSD scheme was found  to be cost-effective, efficient and worked for the integrated development of villages. This indigenous concept of rural  development needs to be considered for upscaling in other parts of the country. The model holds a great hope for  government departments, NGOs and voluntary organizations working at grassroots level.
Keywords: Deendayal research institute; dispute/litigation free villages; gandhi; samaj shilpi dampati; village self reliance campaign